Effectiveness of a New-Generation CEW in Human Subjects with a Goal-Directed Task - Kunz, S. N.; Ho, J. D.; Dawes, D. M.; Knack, S. K. (Human factors and mechanical engineering for defense and safety, 2024)
Conducted electrical weapons (CEWs) have been used by law enforcement agencies worldwide to control and restrain potentially violent persons. As new generations of these weapons are developed, effectiveness and safety need to be evaluated. The new TASER 10 uses an independently targeted probe scheme with floating polarities so that any two probes can form a connection. This is in contrast to older generation weapons, which used paired probes with fixed take-off angles. The expectation is with up to a maximum of 10 shots and independent targeting; the weapon will have a greater effectiveness. In this pilot study, we used our previously published, standardized methodology for measurement of CEW effectiveness on motivated human volunteers for several objectives: (1) to directly compare the effectiveness of the waveform on human subjects to an older generation weapon (the TASER 7), (2) to more broadly compare it to historical controls, and (3) to look at various probe configurations to determine their comparative effectiveness. The task at hand was to reach a suspended martial arts dummy 12 ft (3.65 m) away while being exposed (under power) to the electrical waveform of the TASER devices in various dart configurations. Several intervention groups were examined. We used video review with our standard methodology to rate goal achievement and limb capture. The results demonstrate that the TASER 10 has similar ability to induce neuromuscular incapacitation as the TASER 7. Additionally, the ability of the TASER 10 to place multiple darts on a specific target area to create the desired probe spread is a technological advantage over previous models. This, together with the floating polarity probes, promise to make the TASER 10 potentially more effective and flexible in the field.